AN ANALYSIS OF THE EFFECT OF FOLK DANCES ON VISUAL MOTOR PERCEPTION LEVEL OF PRIMARY SCHOOL FIRST GRADE (7 AGES) STUDENTS. - ATASOY, Murat; ALTUN, Meryem; YALÇINKAYA, Ahmet (Electronic Turkish Studies)
The purpose of this study is to examine the effects of folk dances on visual motor perceptions of primary school primary (7 ages) students. The study was conducted using experimental design with pretest / posttest control group. The study group of the study is composed of seven year old children who are educated in Süleyman Türkmani Primary School in Kırşehir in 2016-2017 educational year and selected by objective sampling method. The study group is a total of 90 people consisting of 45 experiments and 45 controls. "Visual Motor Gestalt Test" was used as the measurement tool in the research. For the experimental group, the folk dances education program was applied as 2 hours a day for 3 days a week for 12 weeks, whereas for the control group only the education was given according to the Ministry of National Education Education Program. The obtained data were analyzed and analyzed using SPSS 22 (Statistical Package for the Social Sciences) package program. In the analysis of the data, the dependent sample t-test was used to examine the differences between the experiment and control groups, while the demographics were examined on the percentage and frequency. As a result of the study, it was seen that there was a significant difference in favor of the experiment group between the visual motor perception levels of children who received the folk dances curriculum and children who received the National Education Ministry Pre-School curriculum. This result shows the effectiveness of folk dances in improving the visual motor perception level. This result shows that folk dances are effective in improving visual motor perception level. There was also no difference in terms of sex. It is thought that sex roles in this age group are not yet evidentsignificant